EFEKTIVITAS LAYANAN M-PASPOR DALAM MEWUJUDKAN ZONA INTEGRITAS WILAYAH BIROKRASI BERSIH DAN MELAYANI PADA KANTOR IMIGRASI KELAS I TPI PEKANBARU - Yuliana, Rima; Heriyanto, Meyzi; Meilani, Nur Laila (Jurnal Progress Administrasi Publik, 2023)
Public service is one of the main roles of government, since government has existed to meet the interests and needs of society or its members throughout history. This includes various activities carried out by public bureaucratic institutions to meet the various needs and interests of the user community. In this regard, to improve the quality of service and create a Clean and Serving Bureaucratic Area (WBBM) in processing passports, the TPI Pekanbaru Class I Immigration Office launched an innovation that can help the public manage services more effectively and efficiently. The innovation is in the form of the M-Paspor application which is designed as an innovation service in mobile form. The aim of this research is to analyze the effectiveness of the M-Passport service in realizing a Clean and Serving Bureaucratic Regional Integrity Zone at the TPI Pekanbaru Class I Immigration Office and to analyze the inhibiting factors in implementing the M-Passport service in realizing a Clean and Serving Bureaucratic Regional Integrity Zone TPI Pekanbaru Class I Immigration Office. The theory used is Suwarto's Effectiveness Theory in Ramayanti, 2022. The research method used is qualitative, explanatory. The results of this research are that the M-Passport service implemented by the Pekanbaru City TPI Class I Immigration Office in realizing a Clean and Serving Bureaucratic Regional Integrity Zone has been running effectively. However, several improvements are still needed to implement several things so that they run in accordance with the main objective of establishing the service.   Keywords: Effectiveness; Public Services; M-Passport; WBBM; Integrity Zone.